Web-Based Café Hopper Platform - MD SARIF, NUR RAUDAH EZATUL; abd ishak, suhaimi (Applied Information Technology And Computer Science, 2025)
The Café Hopper Platform is a web-based solution designed to enhance the café discovery and booking experience for both customers and café owners. Developed using Agile methodologies, the platform offers a centralized hub for locating cafés that align with diverse consumer preferences, such as pet-friendliness or Wi-Fi availability, while promoting visibility for small, local establishments. The front end is built with HTML, CSS, and JavaScript to ensure an intuitive user interface, while the back-end leverages PHP and MySQL for secure data management, process integration, and user authentication. Key features include personalized café search, real-time booking, a payment gateway, and a unique review system. Integrated APIs support location-based search and advanced filtering, and the responsive design ensures usability across devices. Café owners can manage profiles, update information, and interact with customer feedback to boost engagement and reputation. Developed in a prototype scope using Visual Studio Code and XAMPP for the local environment, the platform’s modular architecture enhances scalability and maintainability. By streamlining the café search process and offering robust tools for customer-business interaction, the Café Hopper Platform fosters a thriving café culture and supports the growth of independent café entrepreneurs.